ANALISIS PERILAKU KONSUMSI CERDAS PADA LAYANAN FOOD DELIVERY (GOFOOD/GRABFOOD) DI KALANGAN MAHASISWA: ANALISIS PERILAKU KONSUMSI CERDAS MAHASISWA - Zahra Widia Aristantia; Bahasa Indonesia (Universitas Pasundan, 2025)
The purpose of this study is to examine smart consumption behavior among university student utilizing online food delivery (OFD) service such as GoFood and GrabFood. This study employed a qualitative descriptive method, with data obtained through in depth interviews with student form Pasundan University. The findings indicate that smart consumption behavior is reflected in student ability to compare prices across various platforms, assess restaurant reviews, and set monthly budget limits to avoid rash purchases. While marketing strategies such as large discounts and free delivery often encourage consumer behavior, an understanding of economics and self control play a crucial role in helping students manage their finances wisely. This study concludes that despite high accessibility, digital and economic literacy remain key factors shaping rational consumption habits among generation Z.